Pengaruh Literasi Keuangan, Konformitas Teman Sebaya, dan Kecemasan Finansial terhadap Perilaku Keuangan Generasi Z di Jabodetabek - Zahra, Akmelia; Suparno, Suparno; Lestari, Fitra Dila (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of Financial Literacy, Peer Conformity, and Financial Anxiety on the Financial Behavior of Generation Z in the Greater Jakarta area. This study employed a quantitative approach with an explanatory and cross-sectional design. Data were collected through questionnaires distributed via social media and in person to 196 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS Statistics 32. The results indicate that Financial Literacy has a positive and significant effect on Financial Behavior, while Peer Conformity has a negative and significant effect. Meanwhile, Financial Anxiety has no significant effect on Financial Behavior. The Adjusted R Square value of 0.288 indicates that the three variables explain 28.8% of the variation in Financial Behavior, while the remaining 71.2% is explained by other factors outside the research model. These findings emphasize the importance of financial understanding and independence in financial decision-making among Generation Z.